BIOANALYTICAL METHOD DEVELOPMENT AND VALIDATION OF TICAGRELOR BY RP-HPLC - DCRUZ, Delma; Babu, Anu; Joshy, Eena; P., Aneesh T. (International Journal of Applied Pharmaceutics, 2017)
Objective: The main purpose of this study was to develop a simple, precise, rapid and accurate RP-HPLC method for the quantitative determination of ticagrelor in human plasma. Methods: The separation was accomplished by the isocratic method by utilizing phenomenex C18 column on a Shimadzu binary gradient liquid chromatography system furnished with LC-20AD solvent delivery system, SPD-20-A photo-diode array detector and 20 µl loop volume in a rheodyne injector. The analyte was extracted by protein precipitation in the involvement of diethyl ether as a protein precipitator. The mobile phase was developed for the estimation of the drug in human plasma consists of acetonitrile and methanol in the ratio of 60:40% v/v. Separation was done with a flow rate of 1 ml/min at a detection wavelength of 254 nm. Results: Retention time was found to be 4.503 min with a run time 10 min. Linearity shows in a range of 20-100 µg/ml, with a correlation coefficient of 0.9992 respectively. Stability studies of ticagrelor in plasma were carried out by, short term stability, long term stability and bench top stability studies. Short term stability, long term stability and bench top stability of ticagrelor was carried out from 20 and 100 µg/ml concentration and %RSD was ascertained 0.12% and 0.08%, 0.18% and 0.15%, 1.19% and 1.30% respectively. Conclusion: The outcomes were observed to be inside the knowledge of ICH guidelines. The prepared solution was injected in triplicate, and % RSD was measured. Acquired results demonstrate that proposed strategy can be effortlessly and advantageously applied for routine examination of ticagrelor in human plasma